REPRESENTASI PEREMPUAN DALAM SURAT KABAR Analisis Wacana Kritis Rubrik Tapaleâuk di Surat Kabar Harian Pos Kupang Edisi hari Kartini sejak tahun 2008 hingga 2012 - , HERLYN DJUNINA; , Dr.Phil. Ana Nadhya Abrar, M.E.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It should be roceognized that the local press has the ability is more than just a source of information fot the surrounding community. Local press also has the power to shape publis perception through opinions constructed by mass media. Opinions of media on social problem, it could be the response of the community of readers. But there are also, the opinion of the local press, still affected from the culture that embraced by the community. The presence of women in the community who hold East Nusa Tenggara patrilieal culture, often also became the spotlight in the opinion of local press. This research takes the title âThe Representation of Women in Newspaper (The Critical Discourse Analysis of Rubric Tapaleâuk at the Daily Newspaper the Pos Kupang, in Kartiniâs day Editions from 2008 to 2012). The question in this research is âhow the Rubric Tapaleâuk representing women of East Nusa Tenggara in its media ?. Rubric Tapaleâuk is the rubric that contains media opinion written by using the local language, the Kupangâs language. This research using a method of analysis by Fairclough that explains how discourse practice, process production and socio cultural practical, can form an unified discourse. This study aims to describe how the media in East Nusa Tenggara, especially Rubric Tapaleâuk Pos Kupang, represent women in the discourse. In addition, the study also aims to evaluate how Pos Kupang representing women in society. Results of this study show the representation of women in the rubric Tapaleâuk is as wife and homemaker. However further, every writer in this rubric presents different representation of housewives. Male writers in this rubric, tend to represent women not as a central figure in the text, women often just used only as a complement dressing. While more female writere using text to represent the figure of an intelligent housewife. That figure is not just limited to the housekeeper, but becomes the central figure in the text, who has sense of critical of social problem, dare to break through the culture of patriarchy with many ideas, that are not less on appeal if compared with men.